2003
DOI: 10.1161/01.cir.0000090689.69973.b1
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases as Novel Disease Markers in Takayasu Arteritis

Abstract: Background-Takayasu arteritis (TA) is a chronic vasculitis that primarily affects large elastic arteries. Monitoring of disease activity is crucial because the disease tends to progress despite treatment with glucocorticoid and/or immunosuppressive agents. Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) have generally been used as disease activity markers, but these are nonspecific inflammatory markers and lack the sensitivity and specificity to accurately monitor the disease status. Given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
1
13

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 23 publications
5
78
1
13
Order By: Relevance
“…Thus urinary MMP excretion is not a reflection of increased systemic inflammation and MMP expression. Previously, in systemic lupus erythematosus, giant cell arteritis, and Takayasu arteritis, elevated protein levels and activity of MMP-9 were found, whereas MMP-2 was elevated in Takayasu arteritis (4,11,13). In Wegener's granulomatosis, Bjerkeli (1) found increased plasma MMP levels, including MMP-2.…”
Section: Discussionmentioning
confidence: 96%
“…Thus urinary MMP excretion is not a reflection of increased systemic inflammation and MMP expression. Previously, in systemic lupus erythematosus, giant cell arteritis, and Takayasu arteritis, elevated protein levels and activity of MMP-9 were found, whereas MMP-2 was elevated in Takayasu arteritis (4,11,13). In Wegener's granulomatosis, Bjerkeli (1) found increased plasma MMP levels, including MMP-2.…”
Section: Discussionmentioning
confidence: 96%
“…Usually, surgery or endovascular repair is recommended at a time of quiescent TA disease to avoid complications. 13,24 Matsuyama et al 25 found that increased levels of inflammatory cytokines within the arterial lesions of TA induce production of matrix metalloproteinase (MMP)-3 and MMP-9 from infiltrated mononuclear cells and/or smooth muscle cells, which results in the destruction of elastic fibers in the arterial media. They observed a positive correlation between both MMP-3 and MMP-9 levels and disease activity score, and the elevated levels of MMP-3 and MMP-9 improved when patients entered remission.…”
Section: Discussionmentioning
confidence: 99%
“…They observed a positive correlation between both MMP-3 and MMP-9 levels and disease activity score, and the elevated levels of MMP-3 and MMP-9 improved when patients entered remission. 25 Numano et al 1 advocated that the inflammation caused by TA would result in atherosclerotic lesions of the aorta and arteries. Hypertension, frequently found in patients with TA, may accelerate the atherosclerotic process in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli for synthesis are cytokines, which are inflammatory mediators. Thus some studies suggest that MMP values can also be used as markers of disease activity, for example in rheumatoid arthritis, 37 38 Takayasu arteritis, 39 and giant cell arteritis. 40 We found increased levels of MMP-3, MMP-9, and TIMP-1 in our patients as well.…”
Section: Discussionmentioning
confidence: 99%